Molybdenum abundance in some open clusters - Shereta, E.; Carraro, G.; Gorbaneva, T.; Mishenina, T. (Одеські астрономічні публікації, 2018)
This paper presents the results of determination of the molybdenum abundances in 13 G, K type stars in the open clusters NGC 2477 and NGC 2506. The abundances of molybdenum were determined using stellar atmosphere models by Castelli & Kurucz (2004), as well as a modified STARSP LTE spectral synthesis code (Tsymbal, 1996). For the used Mo I lines 5506 and 5533 Å the oscillator strengths log gf were adopted from the latest version of the VALD database dated 2016 (Kupka et al., 1999). The high resolution spectra were obtained with a VLT telescope at the European Southern observatory (ESO, Chile). We used atmospheric parameters of the investigated stars which we had obtained earlier. We have found out that the molybdenum abundances depend on metallicity [Fe/H] in giants of NGC 2506 and NGC 2477. For the stars in NGC 2506, molybdenum is slightly overabundant as compared to the solar abundance; such an overabundance is slightly higher in the stars of the second investigated cluster NGC 2477. Further investigation of the Mo abundance in larger number of open clusters is required to draw reliable conclusions.